COMPLEXITIES ABOUT SIMPLE HARMONIC MOTION - Jain, H.C. (SCHOOL SCIENCE, 2011)
Study of Simple Harmonic Motion (SHM) is not as simple as it appears to be. It has a number of complexities. The present paper deals with the concepts held by experienced teachers pertaining to sign for displacement, velocity, and acceleration, its effect on speed during different time intervals and direction of acceleration while executing SHM Responses obtained in training programmes have been analysed and indicate several misconceptions. Treating the path of an oscillating pendulum along a straight line particulalry poses a lot of difficulty. In view of these concepts having direct implications on teaching to students, strategy for teaching the related concepts pertaining to SHM, in particular, and problem-solving, in general, using basic cocepts and principles has been emphasised.